2023
DOI: 10.1002/eat.23986
|View full text |Cite
|
Sign up to set email alerts
|

Childhood body mass index and the subsequent risk of anorexia nervosa and bulimia nervosa among women: A large Danish population‐based study

Abstract: ObjectiveEvidence linking childhood body mass index (BMI) with subsequent eating disorders is equivocal. Potential explanations include different study populations and size, and that anorexia nervosa (AN) and bulimia nervosa (BN) should be studied separately. We examined whether birthweight and childhood BMI were associated with subsequent risk of AN and BN in girls.MethodWe included 68,793 girls from the Copenhagen School Health Records Register born between 1960 and 1996 with information on birthweight and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Our findings suggest that the preponderance of premorbid overweight/obesity and higher premorbid BMI in patients with atypical AN (Walsh et al, 2023) is related to the diagnostic weight cutoff. Conversely, the epidemiological associations (Leth-Moller et al, 2023;Stice et al, 2017Stice et al, , 2022Yilmaz et al, 2019) and genetic correlations (Watson et al, 2019) between a low premorbid BMI and AN may partially, if not completely, result from the diagnostic requirement of a 'significantly low body weight' in AN (Leth-Moller et al, 2023). In the second part of our study, exploratory analyses compared AN and atypical AN in terms of weight loss, anthropometric variables, age, and illness duration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our findings suggest that the preponderance of premorbid overweight/obesity and higher premorbid BMI in patients with atypical AN (Walsh et al, 2023) is related to the diagnostic weight cutoff. Conversely, the epidemiological associations (Leth-Moller et al, 2023;Stice et al, 2017Stice et al, , 2022Yilmaz et al, 2019) and genetic correlations (Watson et al, 2019) between a low premorbid BMI and AN may partially, if not completely, result from the diagnostic requirement of a 'significantly low body weight' in AN (Leth-Moller et al, 2023). In the second part of our study, exploratory analyses compared AN and atypical AN in terms of weight loss, anthropometric variables, age, and illness duration.…”
Section: Discussionmentioning
confidence: 93%
“…Compared to patients with atypical AN, there is a lower prevalence of premorbid overweight/obesity and lower maximal BMI in patients with AN (Walsh et al, 2023). Further, epidemiological studies have demonstrated associations between low childhood BMI and increased AN risk (Leth-Moller et al, 2023;Stice et al, 2017Stice et al, , 2022Yilmaz et al, 2019) and genome wide association studies (Duncan et al, 2017;Watson et al, 2019) have identified genetic correlations between AN, low BMI, and associated traits. For example, in the Avon Longitudinal Study of Parents and Children (Abdulkadir et al, 2022), female participants with a high polygenic score for AN and a low polygenic score for BMI constituted a high-risk group for AN.…”
Section: Introductionmentioning
confidence: 99%
“…Prior genetic and epidemiological studies document an association between 'underweight' and AN, insofar as individuals with unique metabolic and anthropomorphic phenotypes corresponding with 'underweight' (e.g., low BMI, percent body fat, and waist circumference) (Watson et al, 2019) and individuals with lower childhood BMIs (Leth-Moller et al, 2023;Stice et al, 2017Stice et al, , 2022Yilmaz et al, 2019) are at heightened risk for developing AN.…”
mentioning
confidence: 99%